Analisis Efisiensi Perencanaan Tahapan Pembangunan dan Pengendalian Bahan Baku Untuk Produksi Pembangunan Rumah Pada CV Tb Putra Mandiri - Yayan Yanuari; Andri Tanu Wijaya (Mulia Pratama, 2021)
Efficient development stages using the CPM method to see and determine which stages can be preceded and accompanied by the achievement of a working time of 61 days in the construction of one housing unit. The number of economical and optimal raw material needs using the EOQ method for sand raw material is 29.85 cubic with an order frequency of 1 time in three months, for cement raw material 219.15 sacks with an order frequency of 1 time in three months and for split is 1.06 cubic with an order frequency of 1 time in three months. The quantity of safety stock or Safety stock using the EOQ method, the quantity of safety stock for sand is 32.34 cubic for cement is 137.5 sack and for split is 2.97 cubic. The reorder point according to the EOQ calculation for sand is at 32.37 cubic for cement at 139.18 sack and 3 cubic. The managerial implementation of CV TB Putra Mandiri regarding the efficient use of raw materials can be done by planning (planning) the needs for the use of raw materials, organizing (organizing) the field of coconut milk production process activities, actuating (implementing) activities in accordance with standard operating procedures (SOPs). Company and controlling (supervision) of raw materials, planning at the stages of the development process.